Subcellular localization of Bcr, Abl, and Bcr-Abl proteins in normal and leukemic cells and correlation of expression with myeloid differentiation. - Wetzler, M (1993)
We used specific antisera and immunohistochemical methods to investigate the subcellular localization and expression of Bcr, Abl, and Bcr-Abl proteins in leukemic cell lines and in fresh human leukemic and normal samples at various stages of myeloid differentiation. Earlier studies of the subcellular localization of transfected murine type IV c-Abl protein in fibroblasts have shown that this molecule resides largely in the nucleus, whereas transforming deletion variants are localized exclusively in the cytoplasm. Here, we demonstrate that the murine type IV c-Abl protein is also found in the nucleus when overexpressed in a mouse hematopoietic cell line. However, in both normal and leukemic human hematopoietic cells, c-Abl is discerned predominantly in the cytoplasm, with nuclear staining present, albeit at a lower level. In contrast, normal endogenous Bcr protein, as well as the aberrant p210BCR-ABL and p190BCR-ABL proteins consistently localize to the cytoplasm in both cell lines and fresh cells. The results with p210BCR-ABL were confirmed in a unique Ph1-positive chronic myelogenous leukemia (CML) cell line, KBM5, which lacks the normal chromosome 9 and hence the normal c-Abl product. Because the p210BCR-ABL protein appears cytoplasmic in both chronic phase and blast crisis CML cells, as does the p190BCR-ABL in Ph1-positive acute leukemia, a change in subcellular location of Bcr-Abl proteins between cytoplasm and nucleus cannot explain the different spectrum of leukemias associated with p210 and p190, nor the transition from the chronic to the acute leukemia phenotype seen in CML. Further analysis of fresh CML and normal hematopoietic bone marrow cells reveals that p210BCR-ABL, as well as the normal Bcr and Abl proteins, are expressed primarily in the early stages of myeloid maturation, and that levels of expression are reduced significantly as the cells mature to polymorphonuclear leukocytes. Similarly, a decrease in Bcr and Abl levels occurs in HL-60 cells induced by DMSO to undergo granulocytic differentiation. The action of p210BCR-ABL and its normal counterparts may, therefore, take place during the earlier stages of myeloid development.